Melatonin in rat pineal gland and serum; rapid parallel decline after light exposure at night - Illnerova, H; Backström, M; Sääf, J; Wetterberg, L; Vangbo, B (Neuroscience letters, 1978)
Melatonin content in the rat pineal decreases at night after exposure of animals to light, from 20 to 2 pmol/gland in 15 min. Melatonin concentration in serum fell precipitously in a manner almost identical to the drop in pineal melatonin only with a 5 min time lag. It is concluded that the rapid decrease in the pineal melatonin content is mainly due to an inhibited synthesis of melatonin.